Double Michael Addition Reactions of the Nazarov Reagent with 2-Cyano-2-Cycloalkenones: An Alternative Approach to cis-Fused Bicyclic Systems - Tu, Che-Hao; Wu, Yen-Ku; Shia, Kak-Shan; Kuo, Sheng-Chu; Liu, Hsing-Jang; Hsieh, Min-Tsang (Synlett, 2014)
A highly stereoselective annulation reaction of 2-cyano-2-cycloalkenones with the Nazarov reagent catalyzed by 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU), leading to densely functionalized bicyclic systems, is developed.
Keywords: bicyclic compounds; α-cyano enones; double Michael addition; annulation; Nazarov reagent